SARS-CoV-2 vertical transmission supports innate fetal protection: A narrative review - Barnea, Eytan R.; Di Simone, Nicoletta; Hayrabedyan, Soren; Todorova, Krassimira; Inversetti, Annalisa; Vento, Giovanni; Costa, Simonetta (Frontiers in Virology, 2022)
Prenatal infections that have been exhaustively studied help frame the current SARS-COV-2 pandemic, with the caveat that asymptomatic SARS-COV-2 infected patients are not tested, while those symptomatic are delivered and/or treated with drug(s) available on-site. Thus, management and therapy are still heterogeneous. SARS-COV-2 induced respiratory infection remains mostly local, unless severe -lessens transplacental vertical transmission (VT). Vaccination prior or during pregnancy significantly changes the prognosis for both mother and newborn. The virus spread to the fetus can be hematogenous as the free virion, or engulfed in immune cells, not affecting the decidua, or in the placenta binding to ACE2 protein receptors, whose expression is low at term. Most placental infections are subclinical unless severe villitis and apoptosis are observed. The placenta is rarely tested, and it is highly probable that most are positive for the virus, requiring sophisticated diagnostics to document. Other VT modalities, such as vaginal, rectal or through amniotic fluid contamination, are very rare. Therefore, vaginal delivery is preferable when clinically feasible. It has not yet been unraveled whether the placenta is a shield or if it transmits infection, while, on the other side, recent data support fetal resilience which is plausible due to the major difference between the placental and fetal rate of infection: only 3-5% of documentable VT compared with up to 100% expected placental exposure to viremia. Newborn Polymerase Chain Reaction (PCR) from nasal swab is more practical as an option for VT diagnosis compared to ocular or anal swab, low yield. The maternal infection leads to antiviral IgG production of 100% in severe cases which are transferred to the fetus and breast milk. Postpartum- documenting VT is difficult since horizontal viral transmission may be common, minimized by mother/staff/family-preventive measures. Breastfeeding is safe and encouraged because, beyond nutrition, it promotes protective antibodies transfer and maternal bonding. Lessons learned from other beta-corona viruses (SARS COV and MERS) virulence are relevant since mutations can increase/decrease vulnerability. Overall, data support fetal/newborn resilience against SARS-CoV-2 VT, however, viremia monitoring by sensitive tests and assessment for delayed sequelae shown in adults is necessary.